2005
DOI: 10.4049/jimmunol.174.8.4836
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphonuclear Neutrophils Improve Replication ofChlamydia pneumoniaeIn Vivo upon MyD88-Dependent Attraction

Abstract: Chlamydia pneumoniae, an obligate intracellular bacterium, causes pneumonia in humans and mice. In this study, we show that GR1+/CD45+ polymorphonuclear neutrophils (PMN) surprisingly increase the bacterial load of C. pneumoniae in vivo. Upon intranasal infection of wild-type mice, the lung weight is increased; the cytokines TNF, IL-12p40, and IFN-γ, as well as the chemokines keratinocyte-derived chemokine, MCP-1, and MIP-2 are secreted; and GR1+/CD45+ PMN are recruited into lungs 3 days postinfection. In cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
70
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 34 publications
9
70
0
Order By: Relevance
“…However, in lungs of TLR2 -/-and TLR2 -/-ÂTLR4 d/d mice the number of C. pneumoniae IFU was lower than in WT or TLR4 d/d mice 3 days post infection (Fig. 4A), a finding which was similar to MyD88 -/-mice [19]. Comparison of chlamydial burden and pulmonary influx of PMN in TLR2 -/-, TLR2 -/-ÂTLR4 d/d , MyD88 -/-and WT mice at day 3 post infection revealed that the two parameters correlated with each other (Fig.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…However, in lungs of TLR2 -/-and TLR2 -/-ÂTLR4 d/d mice the number of C. pneumoniae IFU was lower than in WT or TLR4 d/d mice 3 days post infection (Fig. 4A), a finding which was similar to MyD88 -/-mice [19]. Comparison of chlamydial burden and pulmonary influx of PMN in TLR2 -/-, TLR2 -/-ÂTLR4 d/d , MyD88 -/-and WT mice at day 3 post infection revealed that the two parameters correlated with each other (Fig.…”
Section: Resultssupporting
confidence: 55%
“…In contrast WT mice showed irregularly distributed foci of acute bronchopneumonia with intra-alveolar or intrabronchial aggregates of granulocytes and intense perivascular infiltrates at this point in time, a finding we already observed in MyD88 -/-mice (Fig. 7B) [19]. At 9 days post infection, TLR2 -/-ÂTLR4 d/d mice displayed widespread, acute parenchymal inflammation with epithelial cell necrosis, edema and massive intraalveolar infiltrates of granulocytes and mainly macrophages and lymphocytes, while WT mice still showed significant inflammatory infiltrates, but in addition accumulation of foam cells indicative of resorptive changes (Fig.…”
Section: Development Of Pneumonia In Wt Andsupporting
confidence: 69%
See 1 more Smart Citation
“…Moreover, although chemokine-deficient models have shown increased bacterial burden during Salmonella infection, [19][20][21], it is not known which chemokines are induced in the intestinal lymphoid tissue during oral Salmonella infection or where and by what cells the chemokines are produced. Finally, although impaired recruitment of inflammatory cells in mice deficient in TLR pathways has been observed in some infection models [22,23], the role of the different TLR and the adaptor MyD88 in cell recruitment during oral Salmonella infection is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, although chemokine-deficient models have shown increased bacterial burden during Salmonella infection, [19][20][21], it is not known which chemokines are induced in the intestinal lymphoid tissue during oral Salmonella infection or where and by what cells the chemokines are produced. Finally, although impaired recruitment of inflammatory cells in mice deficient in TLR pathways has been observed in some infection models [22,23], the role of the different TLR and the adaptor MyD88 in cell recruitment during oral Salmonella infection is not known.Thus, the aims of this study were to use an oral Salmonella infection model to: (i) investigate chemokine induction and the cellular sources in the PP and MLN when phagocyte influx is first observed; (ii) localize chemokine production in infected PP using laser capture microdissection microscopy; (iii) assess distribution of phagocytes recruited to infected PP by fluorescence microscopy and (iv) establish the relationship between TLR, chemokine production and phagocyte recruitment. The data provide insight into the chemokine milieu that orchestrates the early recruitment of phagocytes to combat oral Salmonella infection.…”
mentioning
confidence: 99%